To assess the effectiveness of supplier relationship management strategies on service quality: a case of Shomet Construction private limited. - Mutingarife, Vongai (Midlands State University, 2017)
The aim of the research was to assess the effectiveness of supplier relationship management strategies on service quality. The objectives of the research were to assess the effectiveness of value creation strategy on service quality, to assess the effectiveness of supplier account management strategy on service quality and to assess the effectiveness of joint venture strategy on service quality. Relevant literature on the effectiveness of value creation strategy, supplier account management strategy and joint venture strategy on service quality was reviewed from different authors. The study emanated from Shomet Construction’s lack of financial resources and delays in payment to its suppliers due to the liquidity crunch the country is facing ; and complaints from customers about high costs in terms of prices and delayed delivery of services due to high costs incurred by the company in the process of service delivery which include complaint investigations and inspections. The researcher used the explorative and descriptive research designs to gather data where interviews and questionnaires were done using simple random sampling and purposive sampling techniques. A sample size of thirteen (13) respondents consisting of two (2) service operations management and eleven (11) organizational customers was used for the research. The analysis of the research findings with the help of hypothesis testing showed that there is a strong relationship between value creation strategy and service quality as show by the correlation of 0.8740 and regression with p value 0.002 and t value 4.76, the researcher concluded that there is a strong positive relationship between the variables and that the company should reject H0 and accept H1 and recommended that it should continue using the strategy. The hypothesis testing showed that there is a strong positive relationship between supplier account management strategy and service quality as show by the correlation of 0.8974 and regression with p value 0.001 and t value 5.38, the researcher concluded that there is a relationship between the variables and that the company should reject H0 and accept H2 and recommended that it should continue using the strategy. The hypothesis testing showed that there is a moderate relationship between joint venture strategy and service quality as show by the correlation of 0.8357 and regression p value 0.005 and t value 4.03, the researcher concluded that there is a relationship between the variables and that the company should reject the H0 and accept the H3 and recommended that it should continue using the strategy.